Exploring 2D Energy Storage Materials: Advances in Structure, Synthesis, Optimization Strategies, and Applications for Monovalent and Multivalent Metal‐Ion Hybrid Capacitors. Issue 50 (26th October 2022) - Wu, Mengcheng; Zheng, Wanying; Hu, Xi; Zhan, Feiyang; He, Qingqing; Wang, Huayu; Zhang, Qichun; Chen, Lingyun
Abstract: The design and development of advanced energy storage devices with good energy/power densities and remarkable cycle life has long been a research hotspot. Metal‐ion hybrid capacitors (MHCs) are considered as emerging and highly prospective candidates deriving from the integrated merits of metal‐ion batteries with high energy density and supercapacitors with excellent power output and cycling stability. The realization of high‐performance MHCs needs to conquer the inevitable imbalance in reaction kinetics between anode and cathode with different energy storage mechanisms. Featured by large specific surface area, short ion diffusion distance, ameliorated in‐plane charge transport kinetics, and tunable surface and/or interlayer structures, 2D nanomaterials provide a promising platform for manufacturing battery‐type electrodes with improved rate capability and capacitor‐type electrodes with high capacity. In this article, the fundamental science of 2D nanomaterials and MHCs is first presented in detail, and then the performance optimization strategies from electrodes and electrolytes of MHCs are summarized. Next, the most recent progress in the application of 2D nanomaterials in monovalent and multivalent MHCs is dealt with. Furthermore, the energy storage mechanism of 2D electrode materials is deeply explored by advanced characterization techniques. Finally, the opportunities and challenges of 2D nanomaterials‐based MHCs are prospected. Abstract : This review provides a comprehensive and in‐depth understanding of the structure–performance relationship and underlying mechanisms of 2D nanomaterials for various monovalent and multivalent metal‐ion hybrid capacitors. Finally, prospects and challenges for further development are proposed.